Developing a robotic process automation management model - Sobczak, Andrzej (Budowa modelu zarządzania robotyzacją procesów biznesowych, 2019)
One of the distinguishing features of digital transformation is the large scale business process automation, and, in particular, robotic process automation – with the use of software from the currently growing RPA (Robotic Process Automation) category. This is such a new field that a commonly accepted conceptual apparatus (terminology) has not been developed yet, also methodical tools for effective robotic process automation management are missing. Based on the above observations it was deemed justified to conduct research aimed at: (G1): developing a ”robotic process automation” definition proposal, (G2): identifying the key ”robotic process automation” management aspects in Polish medium and large enterprises; (G3): developing a robotic process automation management model structure and completing its initial verification. The outcome of the research conducted is the development of a proprietary robotic process automation management model structure that was initially verified at one of companies
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 2 (52), s. 85-100
Keywords: robotic process automation; business process; hybrid work environment; robotyzacja procesów biznesowych; procesy biznesowe; hybrydowe środowisko pracy